2019
DOI: 10.3390/cells8111463
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptors and Melanoma: A Review

Abstract: In the last three decades cutaneous melanoma has been widely investigated as a steroid hormone-sensitive cancer. Following this hypothesis, many epidemiological studies have investigated the relationship between estrogens and melanoma. No evidence to date has supported this association due to the great complexity of genetic, external and environmental factors underlying the development of this cancer. Molecular mechanisms through which estrogen and their receptor exert a role in melanoma genesis are still unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 107 publications
1
60
1
2
Order By: Relevance
“…The levels of circulating hormones increase during puberty and may play a role in melanoma initiation and progression in predisposed individuals through binding to specific sex steroid receptors. Estrogens exert their functions through estrogen receptor (ER)α and ERβ, which are members of the nuclear receptor superfamily of transcription factors (10,11). Both receptors share the same general structure, with three interacting functional domains: The N-terminal domain, DNA-binding domain and ligand-binding domain (LBD or D/E/F).…”
Section: Melanoma and Sex Hormones Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…The levels of circulating hormones increase during puberty and may play a role in melanoma initiation and progression in predisposed individuals through binding to specific sex steroid receptors. Estrogens exert their functions through estrogen receptor (ER)α and ERβ, which are members of the nuclear receptor superfamily of transcription factors (10,11). Both receptors share the same general structure, with three interacting functional domains: The N-terminal domain, DNA-binding domain and ligand-binding domain (LBD or D/E/F).…”
Section: Melanoma and Sex Hormones Exposurementioning
confidence: 99%
“…The LBD is also responsible for binding to co-regulatory and chaperone proteins. Concurrently, the same ligand may have different binding affinities for the ERα or ERβ subtypes (10,11). Since endogenous estrogens, such as estradiol, bind to the two receptors with the same affinity, the net effect on the tissue varies based on the ERα/ERβ ratio in the tissue and the microenvironment of the cells (11).…”
Section: Melanoma and Sex Hormones Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Another unanswered question is whether the effects of female hormones on the immune system may play some role in the improved survival [43], particularly as some series reported less sex-related effects in women over 60 years of age. It is also notable that KDM6A expression (but not KDM6B) is higher in female endocrine tissues and lymphoid tissue [8,43,44]. It is generally recognized that females have higher CD4 T cell levels and lower Treg cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, in 2012, the Australian age-adjusted death rate for females was approximately 2 per 100,000 of the population compared to 5 per 100,000 in males ( ). A number of reasons for the female survival advantage have been proposed, such as behavioral differences in sun exposure, leading to differences in incidence and stage at diagnosis [ 4 ], presentation of males with more advanced thicker melanoma [ 5 , 6 ], higher mutation rates in melanoma from males [ 7 ], and inhibition by estrogens in females (reviewed in [ 8 ]). Nevertheless, multivariate analyses in a number of studies have confirmed that the female sex is an independent prognostic indicator in survival from melanoma [ 1 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%